Graphene / carbon nanotube composite material for field emission cathode and preparation method thereof

CN122979876APending Publication Date: 2026-10-27CHONGQING DONGPAN CARBON MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611180837.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0012]本发明旨在解决现有立式石墨烯场发射阴极存在的发射尖端不足、场屏蔽效应严重、大电流稳定性差的技术问题,提供一种结合网格状基底、立式石墨烯生长和低密度碳纳米管原位生长的三级复合结构场发射阴极的制备方法

Benefits of technology

1. 三级协同结构,性能全面跃升:

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a graphene / carbon nanotube composite material for field emission cathode and a preparation method thereof, relates to the field of carbon nanometer material and cold cathode field emission technology, and discloses the following steps: first, a grid-shaped vertical graphene matrix is obtained by adopting laser etching and plasma-enhanced vapor deposition; then, a catalyst is loaded on the surface of the vertical graphene; and finally, self-supporting carbon nanotubes are in-situ grown on the surface of the vertical graphene by adopting chemical vapor deposition, so that a field emission cathode material based on a grid-shaped vertical graphene in-situ grown self-supporting carbon nanotube array is obtained. The application not only solves the problems of easy agglomeration and difficult dispersion of graphene and carbon nanotubes, and the problems of random combination, serious field shielding effect and the like, but also fully utilizes the electron tunneling effect of the vertical graphene and the self-supporting carbon nanotubes at the tip edges, so that the field emission sites are significantly expanded, and the field emission performance and service life are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon nanomaterials and cold cathode field emission technology, specifically to a graphene / carbon nanotube composite material for field emission cathodes and its preparation method. Background Technology

[0002] Field emission cold cathode devices have wide applications in flat panel displays, X-ray sources, microwave devices, electron microscopes, and other fields. An ideal cold cathode material should possess characteristics such as a low turn-on electric field, high emission current density, high stability, and long lifetime. Currently, commonly used field emission cathode materials mainly include metallic materials, silicon-based materials, semiconductor materials, and carbon-based materials, but each has its own technological bottlenecks.

[0003] Metallic materials (such as molybdenum, tungsten, and cobalt) were the earliest field emission cathodes. High current densities can be achieved by fabricating micro-tip arrays (such as Spindt cathodes), but this process is complex, costly, and suffers from poor uniformity over large areas. Furthermore, metallic micro-tip materials are prone to tip passivation due to ion bombardment and Joule heating during prolonged operation, leading to decreased emission stability.

[0004] Silicon-based materials (such as silicon nanowires and silicon carbide) are compatible with semiconductor processes, enabling the fabrication of micro and nanostructures. However, silicon materials have a high work function, low emission current density, and limited thermal conductivity, making them prone to structural damage due to heat accumulation under high currents. While silicon carbide offers better thermal stability, its fabrication requires high temperatures and is costly, and the emission site density is difficult to control.

[0005] One-dimensional carbon nanomaterials (such as carbon nanotubes) are considered ideal field emitters due to their extremely high aspect ratio and nanoscale tips. Studies have shown that low-density, highly oriented carbon nanotube arrays exhibit lower turn-on electric fields and higher field enhancement factors. However, the density of carbon nanotubes has a decisive impact on performance: too low a density results in insufficient emission tips and limited current density; too high a density leads to strong field shielding effects between adjacent carbon nanotubes, reducing effective emission capability and causing localized overheating and structural damage. Furthermore, the adhesion between carbon nanotubes and metal substrates is weak, making them prone to detachment and affecting device lifespan.

[0006] Vertical graphene is an emerging two-dimensional carbon nanomaterial with a unique upright sheet structure, abundant sharp edges, ultra-high specific surface area, and good electrical conductivity. Its non-stacked morphology overcomes the tendency of graphene to aggregate, increases the heat dissipation area, and is considered one of the ideal cathode materials for field emission devices. However, vertical graphene still has the following prominent problems:

[0007] (1) Limited emission sites: Field emission electrons are mainly concentrated at the top edge of vertical graphene, the main body of the sheet contributes very little to the emission, the effective emission area is insufficient, and the actual emission current density is far lower than the theoretical value.

[0008] (2) Severe field shielding effect: The mutual interference of electric fields between adjacent vertical graphene sheets creates a shielding effect, which weakens the electric field in the middle region, increases the turn-on electric field, and decreases the emission current.

[0009] (3) Poor stability under high current: Under long-term and high current density operation, the emitter tip is damaged by Joule heat accumulation (such as edge collapse and layer breakage), the current decay is obvious, and the device life is limited.

[0010] To improve the field emission performance of vertical graphene, researchers have mainly explored two strategies: one is to combine it with nanomaterials such as carbon nanotubes to increase the number of emission tips; the other is to change the arrangement of vertical graphene through mesh-like growth to weaken the field shielding effect. However, existing technologies mostly use these two strategies in isolation, failing to leverage their synergistic advantages. While combining carbon nanotubes alone increases the number of tips, the aggregation and field shielding problems of the carbon nanotubes themselves are difficult to solve; while a single mesh-like structure improves the macroscopic arrangement, the number of emission tips within a single pattern remains limited.

[0011] Therefore, how to develop a method for preparing a vertical graphene / carbon nanotube multi-level composite field emission cathode based on a mesh substrate is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0012] This invention aims to address the technical problems of existing vertical graphene field emission cathodes, such as insufficient emission tips, severe field shielding effects, and poor high-current stability. It provides a method for preparing a three-tiered composite field emission cathode that combines a mesh substrate, vertical graphene growth, and in-situ growth of low-density carbon nanotubes. By weakening macroscopic field shielding and increasing nucleation sites through the mesh substrate, providing vertical electron transport channels through the vertical graphene, and providing numerous nanoscale emission tips through the low-density carbon nanotubes, the three elements work synergistically to significantly reduce the turn-on electric field and threshold electric field, thereby improving the emission current density and long-term operational stability.

[0013] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a graphene / carbon nanotube composite material for a field emission cathode includes the following steps: (1) The nickel sheet is used as a substrate. It is polished to remove the surface oxide film and scratches. Then it is ultrasonically cleaned in acetone and alcohol respectively. Finally, it is dried with high-purity nitrogen. Then, the nickel sheet substrate is etched in a grid pattern by laser. The pattern shape of the nickel substrate is adjusted by controlling the number of pixels and the scanning speed of laser etching to obtain a grid-shaped nickel sheet substrate. (2) The mesh-like nickel sheet substrate obtained in step (1) is placed in a plasma-enhanced chemical vapor deposition chamber, heated in a reducing atmosphere, and carbon source gas is introduced to grow vertical graphene in situ on the surface of the mesh-like nickel sheet to obtain mesh-like vertical graphene. (3) Place the grid-like vertical graphene obtained in step (2) on the sample stage of the spin coater, and use spin coating to uniformly load the dispersion of oleic acid-coated iron oxide nanoparticles onto its surface, so that the dispersion can be fully spread and penetrate into the gaps and edge areas of the vertical graphene sheets; remove excess dispersion by high-speed rotation, control the catalyst loading and achieve uniform distribution of a single layer, heat and dry to remove solvent, and vacuum dry and heat after spin coating to remove the oleic acid ligands on the surface of the iron oxide nanoparticles, to obtain vertical graphene loaded with catalyst. (4) The vertical graphene loaded with catalyst obtained in step (3) is placed in a chemical vapor deposition furnace, and reducing gas and carbon source gas are introduced. By controlling the vapor growth temperature, time and carbon source gas, a field emission cathode material based on the in-situ growth of self-supporting carbon nanotube arrays of grid-like vertical graphene is finally obtained.

[0014] The self-supporting carbon nanotubes have a length of 0.5-2 μm and an outer diameter of 10-50 nm. The spacing between adjacent carbon nanotubes in the array is 0.5-2 μm, forming a low-density, highly oriented array.

[0015] Further, in step (1), the 0.5 mm thick nickel sheet is cut into 10×10 mm substrates and polished with 400 grit, 800 grit and 1200 grit sandpaper in sequence using a polishing machine to remove the surface oxide film and scratches. Then, it is ultrasonically cleaned in acetone and alcohol for 15 minutes respectively, and repeated twice.

[0016] Furthermore, in step (1), the number of pixels etched by the laser is 50×50, 100×100, 150×150, or 200×200, and the scanning speed is 50-800 mm / s.

[0017] Furthermore, in step (1), the pattern shape is a preset micron-level pattern, which can be a rectangular pattern, a rhombus pattern, a circular pattern, or a customized graphic.

[0018] Furthermore, in step (2), the growth conditions for the vertical graphene are: temperature 800-900℃, flow ratio of methane gas to hydrogen gas 1:(1-5), pressure 50-100 Torr, and time 0.5-2.0 h.

[0019] Further, in step (3), the concentration of the iron oxide nanoparticle dispersion is 0.2-1.0 mg / mL, preferably 0.5 mg / mL, the solvent is n-hexane, and the spin coating process parameters are: the first stage rotation speed is 300-800 rpm, preferably 500 rpm, the time is 5-15 s, preferably 10 s, so that the dispersion can be fully spread and penetrate into the gaps and edge areas of the vertical graphene sheets; the second stage rotation speed is 1000-4000 rpm, preferably 2000 rpm, the time is 20-60 s, preferably 30 s, the number of spin coatings is 1-5 times, preferably 2-3 times, and between each two spin coatings, the particles are heated and dried at 60-80℃ for 2-5 min to remove the solvent. After spin coating, the particles are vacuum dried and heated at 150-300℃, preferably 350℃ for 1-3 hours, preferably 3 hours, to remove the oleic acid ligands on the surface of the iron oxide nanoparticles, so as to obtain vertical graphene loaded with catalyst.

[0020] Furthermore, in step (3), the nanocatalyst is a composite of one or more of iron oxide, cobalt oxide or nickel oxide, and its average particle size is 10-50 nm.

[0021] Further, in step (4), a reducing gas and a carbon source gas are introduced at 700-800℃. The carbon source gas is methane, ethylene or acetylene, and the reducing gas is hydrogen. The flow ratio of the carbon source gas to the hydrogen is 1:(1-5). The growth temperature is 600-900℃ and the growth time is 0.5-2.0h.

[0022] The present invention also provides a graphene / carbon nanotube composite material for field emission cathode prepared by the preparation method described above.

[0023] Compared with the prior art, the present invention has the following outstanding advantages: 1. Three-tier collaborative structure, resulting in a comprehensive performance leap: This invention is the first to integrate a three-tiered structure of laser-etched mesh substrate, vertical graphene, and low-density carbon nanotubes into a single unit: (1) The grid-like substrate weakens the field shielding effect between emitters from a macroscopic perspective, increases the nucleation sites, and forms a carburized layer to enhance electron transport and heat dissipation; (2) The grid-like vertical graphene provides vertically oriented electron transport channels and framework, and its sharp edges are also effective emission sites; (3) Low-density carbon nanotubes provide a massive amount (density approximately 10) of carbon nanotubes. 8 -10 9 cm -2 Furthermore, the independent nanoscale emission tips significantly increase the effective emission area.

[0024] The three elements work together to achieve a "1+1+1>3" effect, overcoming the limitations of single or two-level structures in terms of performance.

[0025] 2. Excellent field emission performance: 1) The turn-on electric field is significantly reduced: Under the same test conditions (electrode spacing 400 μm, vacuum degree <1×10⁻⁶), the electric field is significantly reduced. -5 The turn-on electric field (@10 μA / cm²) of the mesh-like vertical graphene / carbon nanotube composite material prepared in this invention is consistent with the current density definition standard (Pa). 2 The value was 0.60 V / μm, which is about 51% lower than that of pure vertical graphene prepared under the same conditions (1.23 V / μm), indicating that the three-level composite structure of the present invention makes electron emission easier to trigger.

[0026] (2) The threshold electric field is significantly reduced: the threshold electric field (@10 mA / cm 2 The field emission efficiency was 1.03 V / μm, which is about 46% lower than that of pure vertical graphene (1.91 V / μm), further verifying the enhancement effect of the tertiary structure on field emission performance.

[0027] (3) Significantly improved current density: The maximum current density can reach 251 mA / cm² 2 (@2.48 V / μm), is pure vertical graphene (102 mA / cm). 2 The effective emission area and the number of emission tips are 2.5 times that of the low-density carbon nanotube array, showing that the synergistic effect of the mesh substrate and the low-density carbon nanotube array significantly increases the effective emission area and the number of emission tips.

[0028] (4) The field enhancement factor is significantly improved: the field enhancement factor β1 in the low field region is 19480, which is 2.8 times that of pure vertical graphene (6955); the field enhancement factor β2 in the high field region is 36713, which is 3.1 times that of pure vertical graphene (11786). This significant improvement is attributed to the local electric field enhancement effect of the mesh-like edge, the sharp edge of the vertical graphene itself, and the triple superposition enhancement of the low-density carbon nanotube tip, which makes the local electric field intensity much higher than the applied electric field.

[0029] (5) Significantly improved stability: After 60 minutes of continuous operation at a high current (5.5 mA), the current retention rate reached 93%, while pure vertical graphene only retained 77% at a lower current (2.5 mA). At the same initial current density (approximately 33 mA / cm²), the current retention rate was significantly improved. 2 Based on the standard, the current decay rate of the present invention is only 1 / 3 of that of pure vertical graphene, indicating that multi-point emission and grid-like heat dissipation channels effectively suppress structural damage caused by Joule heat accumulation.

[0030] 3. Excellent stability under high current: (1) Multi-point emission reduces heat load: The large number of independent tips provided by low-density carbon nanotubes distribute the emission current. The current carried by a single tip is small, the Joule heat generation is low, and local overheating is avoided.

[0031] (2) Mesh-like structure enhances heat dissipation and adhesion: The nickel particles formed by laser etching and the mesh-like vertical graphene form an embedded interface with a large contact area and strong bonding force; at the same time, this interface can serve as an efficient heat dissipation channel to accelerate heat release.

[0032] (3) Experimental data: After continuous operation at a high current of 5.5 mA for 60 minutes, the current retention rate reached 93%, far exceeding that of pure vertical graphene (77%) and non-mesh vertical graphene / carbon nanotubes (86%). Scanning electron microscopy and transmission electron microscopy observations showed that after testing, the composite material of the present invention only had a small amount of carbon nanotube tip passivation, and the overall structure remained intact, while the comparison sample showed large-area collapse and edge damage.

[0033] 4. Simple process and controllable cost: The laser etching and chemical vapor deposition methods used in this invention are both mature industrial technologies with highly versatile equipment, enabling mass production on large-area substrates. Nickel substrates are inexpensive, gas consumption is low, and the overall manufacturing cost is far lower than traditional Spindt cathode or photolithography-deposition processes.

[0034] 5. Highly applicable: The method of this invention is not only applicable to grid patterns, but can also be extended to any customized graphics (such as school badges, text, complex arrays, etc.) to realize the graphic customization of field emission cathodes and meet the needs of different application scenarios. Detailed Implementation

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Example 1 This embodiment verifies the impact of laser etching pixel count and scanning speed on product performance.

[0037] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 50×50, and the scanning speed is 50 mm / s.

[0038] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0039] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0040] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0041] The self-supported carbon nanotubes obtained in this embodiment have a length of 0.5-2 μm, an outer diameter of 10-50 nm, and a spacing of 0.5-2 μm between adjacent carbon nanotubes, forming a low-density, highly oriented array.

[0042] Example 2 This embodiment verifies the impact of different preset micron-level patterns on product performance.

[0043] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The preset micron-level pattern is a rhombus pattern. The number of pixels etched by the laser is 100×100, and the scanning speed is 100 mm / s.

[0044] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0045] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0046] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0047] The self-supported carbon nanotubes obtained in this embodiment have a length of 0.5-2 μm, an outer diameter of 10-50 nm, and a spacing of 0.5-2 μm between adjacent carbon nanotubes, forming a low-density, highly oriented array.

[0048] Example 3 This embodiment verifies the impact of vertical graphene growth conditions (temperature, flow ratio, pressure, and time) on product performance.

[0049] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0050] (2) The mesh-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 800°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:5, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the mesh-shaped nickel sheet under a pressure of 50 Torr for 0.5 h.

[0051] (3) The grid-like vertical graphene obtained in step two was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using a spin coating method. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0052] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0053] The self-supported carbon nanotubes obtained in this embodiment have a length of 0.5-2 μm, an outer diameter of 10-50 nm, and a spacing of 0.5-2 μm between adjacent carbon nanotubes, forming a low-density, highly oriented array.

[0054] Example 4 This embodiment verifies the impact of different types of nanocatalysts and their loading conditions on product performance.

[0055] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0056] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0057] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated cobalt oxide nanoparticle dispersion (concentration 0.5 mg / mL, average particle size 10 nm, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 150℃ for 1 hour to remove the oleic acid ligands on the surface of the cobalt oxide nanoparticles.

[0058] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0059] The self-supported carbon nanotubes obtained in this embodiment have a length of 0.5-2 μm, an outer diameter of 10-50 nm, and a spacing of 0.5-2 μm between adjacent carbon nanotubes, forming a low-density, highly oriented array.

[0060] Example 5 This embodiment verifies the impact of carbon nanotube growth conditions (type of carbon source gas, flow ratio, growth temperature, and growth time) on product performance.

[0061] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0062] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0063] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0064] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of methane and hydrogen gas (methane:hydrogen = 1:5, volume ratio) was introduced at 600°C. The reaction was carried out for 0.5 hours to obtain a field emission cathode material based on the in-situ growth of self-supporting carbon nanotube arrays of grid-like vertical graphene.

[0065] The self-supported carbon nanotubes obtained in this embodiment have a length of 0.5-2 μm, an outer diameter of 10-50 nm, and a spacing of 0.5-2 μm between adjacent carbon nanotubes, forming a low-density, highly oriented array.

[0066] Comparative Example 1 This comparative example corresponds to Example 1 and verifies the impact of excessively large number of laser etching pixels and excessively fast scanning speed on product performance.

[0067] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 200×200, and the scanning speed is 800 mm / s.

[0068] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0069] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0070] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0071] In the product obtained in this comparative example, the excessive number of pixels resulted in a small pattern size and dense edge spacing, which enhanced the field shielding effect of the carbon nanotube array. At the same time, the excessively fast scanning speed resulted in insufficient surface roughness of the nickel sheet, reduced nucleation sites, and decreased vertical graphene growth density. As a result, the field emission performance of the final product was lower than that of Example 1.

[0072] Comparative Example 2 This comparative example corresponds to Example 2 and verifies the impact of no preset pattern (i.e., a smooth and flat nickel substrate) on product performance.

[0073] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10 × 10 mm substrates. Polish the substrates sequentially with 400 grit, 800 grit, and 1200 grit sandpaper using a polishing machine to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Do not perform laser etching, ensuring that the nickel sheet surface remains smooth and flat without any pre-set micron-level patterns.

[0074] (2) The unetched nickel substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the nickel substrate under a pressure of 70 Torr for 100 min.

[0075] (3) The vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using a spin coating method. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0076] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on the in-situ growth of self-supporting carbon nanotube arrays of vertical graphene was obtained.

[0077] In the product obtained in this comparative example, since there is no grid pattern on the nickel sheet surface, the vertical graphene is uniformly but randomly distributed on the substrate surface, and the field shielding effect between adjacent graphene sheets is severe. At the same time, the lack of nickel particle accumulation sites at the edge of the pattern results in a lower growth density and uniformity of vertical graphene than in Example 2. The field emission performance of the final product (especially in terms of high current stability) is lower than that of Example 2.

[0078] Comparative Example 3 This comparative example corresponds to Example 3, verifying the impact of deviations from the preferred range of vertical graphene growth conditions (too low temperature, too high flow ratio, too low pressure, too short time) on product performance.

[0079] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0080] (2) The mesh-shaped nickel sheet substrate is placed in a plasma-enhanced chemical vapor deposition chamber and heated to 700℃ (below 800℃) under a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:8, volume ratio, exceeding the range of 1:1 to 1:5) is introduced. Vertical graphene is grown in situ on the surface of the mesh-shaped nickel sheet under a pressure of 30 Torr (below 50 Torr) for a growth time of 0.3 h (shorter than 0.5 h).

[0081] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0082] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0083] In the product obtained in this comparative example, the growth temperature was too low, resulting in insufficient methane cracking and insufficient concentration of carbon free radicals; the flow rate ratio was too high, resulting in excessive hydrogen etching; the pressure was too low, resulting in insufficient plasma density; and the time was too short, resulting in small vertical graphene sheet size and incomplete growth. The combination of these factors led to low graphitization degree and excessive defects in the vertical graphene, and the final product's field emission performance (especially current density) was lower than that of Example 3.

[0084] Comparative Example 4 This comparative example corresponds to Example 4, verifying the impact of deviations from the preferred range in the type of nanocatalyst and loading conditions (using nickel oxide, excessively large particle size, excessively high drying temperature, and excessively long drying time) on product performance.

[0085] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0086] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0087] (3) The grid-like vertical graphene obtained in step (2) was placed on the sample stage of a spin coater, and the oleic acid-coated nickel oxide nanoparticle dispersion (concentration 0.5 mg / mL, average particle size 80 nm, exceeding the 10-50 nm range, solvent n-hexane) was uniformly loaded onto its surface using spin coating. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the spin coating was heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the surface of the nickel oxide nanoparticles was vacuum dried and heated at 400℃ for 5 hours (exceeding the 1-3 h range) to remove the oleic acid ligands on the surface of the nickel oxide nanoparticles.

[0088] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0089] In the product obtained in this comparative example, the nickel oxide catalyst exhibited poor dispersion uniformity on the vertical graphene surface, easily agglomerating into large-sized particles; the excessively large 80 nm particle size resulted in a small specific surface area and low catalytic activity; the excessively high drying temperature of 400℃ caused sintering and agglomeration of the catalyst particles; and the excessively long drying time of 5 hours led to over-oxidation or agglomeration of the catalyst. The combined effect of these factors resulted in uneven carbon nanotube growth, low density, and a predominantly bent and entangled state, ultimately leading to a lower field emission performance than in Example 4.

[0090] Comparative Example 5 This comparative example corresponds to Example 5 and verifies the impact of carbon nanotube growth conditions deviating from the preferred range (using ethylene as the carbon source, excessively high flow ratio, excessively low growth temperature, and excessively short growth time) on product performance.

[0091] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0092] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0093] (3) The grid-like vertical graphene obtained in step two was placed on the sample stage of a spin coater, and the oleic acid-coated iron oxide nanoparticle dispersion (concentration 0.5 mg / mL, solvent n-hexane) was uniformly loaded onto its surface using a spin coating method. The spin coating process parameters were: first stage rotation speed 500 rpm, time 10 s; second stage rotation speed 2000 rpm, time 30 s; the number of spin coatings was 3, and the particles were heated and dried at 60℃ for 2 min between each two spin coatings. After spin coating, the particles were vacuum dried and heated at 350℃ for 3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles.

[0094] (4) The vertical graphene loaded with catalyst is placed in a chemical vapor deposition furnace, and a mixture of ethylene and hydrogen gas (ethylene:hydrogen = 1:8, volume ratio, exceeding the range of 1:1~1:5) is introduced at 550℃ (below 600℃) and reacted for 0.3 hours (less than 0.5 h) to obtain a field emission cathode material based on the in-situ growth of self-supporting carbon nanotube arrays of grid-like vertical graphene.

[0095] In the product obtained in this comparative example, the growth temperature of 550°C was too low, resulting in insufficient ethylene cracking and inadequate carbon source supply; the hydrogen ratio in the ethylene:hydrogen ratio of 1:8 was too high, causing excessive etching of the carbon nanotubes; and the growth time of 0.3 h was too short, resulting in insufficient carbon nanotube length (<0.5 μm) and incomplete growth. The combination of these factors led to a sparse and discontinuous carbon nanotube array, an insufficient number of effective emission tips, and ultimately, the field emission performance (especially current density and field enhancement factor) of the product was lower than that of Example 5.

[0096] Comparative Example 6 This comparative example verifies the impact of Fe3O4 nanoparticles without oleic acid coating (i.e., without surfactant protection) as a catalyst on product performance, demonstrating the crucial role of oleic acid coating in catalyst dispersibility and final product performance.

[0097] A method for preparing graphene / carbon nanotube composite materials for field emission cathodes includes the following steps: (1) Cut a 0.5 mm thick nickel sheet into 10×10 mm substrates and polish them sequentially with 400 grit, 800 grit, and 1200 grit sandpaper to remove the surface oxide film and scratches. Then, ultrasonically clean the substrates in acetone and alcohol for 15 minutes each, repeating the process twice. Finally, dry the substrates with high-purity nitrogen. Then, use a laser to perform grid-like etching on the nickel substrates. The number of laser-etched pixels is 100×100, and the scanning speed is 100 mm / s.

[0098] (2) The grid-shaped nickel sheet substrate was placed in a plasma-enhanced chemical vapor deposition chamber and heated to 880°C in a reducing atmosphere. A mixture of methane and hydrogen gas (methane:hydrogen = 1:4, volume ratio) was introduced, and vertical graphene was grown in situ on the surface of the grid-shaped nickel sheet under a pressure of 70 Torr for 100 min.

[0099] (3) Add 0.5 mmol of acetylacetone iron, 2 mmol of 1,2-dodecanediol, and 10 mL of dibenzyl ether to a three-necked flask in sequence (without adding oleic acid and oleylamine), and mix thoroughly by mechanical stirring. Heat to 300 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and reflux for 20 minutes. After the reaction is complete, allow to cool to room temperature naturally, add ethanol and centrifuge (8000 rpm, 10 minutes), discard the supernatant, and wash the precipitate three times with a hexane / ethanol mixture. Finally, disperse the collected black precipitate in hexane to obtain an oleic acid-free Fe3O4 nanoparticle dispersion (concentration 0.5 mg / mL). Place the grid-like vertical graphene obtained in step 2 on the sample stage of a spin coater, and spin coat the above oleic acid-free Fe3O4 nanoparticle dispersion onto its surface. The spin coating process parameters are as follows: first stage spin speed 500 rpm, time 10 s; second stage spin speed 2000 rpm, time 30 s; spin coating is performed 3 times, with heating and drying at 60℃ for 2 min between each two spin coatings. After spin coating, vacuum drying is carried out at 350℃ for 3 hours.

[0100] (4) The vertical graphene loaded with catalyst was placed in a chemical vapor deposition furnace, and a mixture of acetylene and hydrogen gas (acetylene: hydrogen = 10 sccm: 30 sccm) was introduced at 750°C. After reacting for 30 minutes, a field emission cathode material based on a self-supporting carbon nanotube array grown in situ from grid-like vertical graphene was obtained.

[0101] In the product obtained in this comparative example, since the Fe3O4 nanoparticles were not coated with oleic acid, they lacked the protection of steric hindrance in the dispersion and during spin coating. Van der Waals forces dominated between the particles, leading to severe agglomeration of the Fe3O4 nanoparticles on the vertical graphene surface, forming numerous large-sized catalyst clusters. During CVD growth, these agglomerated catalyst particles exhibited reduced catalytic activity due to their excessive size. Furthermore, the carbon nanotubes were randomly entangled and exhibited uneven density (locally overly dense, locally sparse), significantly enhancing the field shielding effect between adjacent carbon nanotubes and reducing the number of effective emission tips. The final product's field emission performance (including turn-on electric field, maximum current density, and stability) was lower than that of Example 3, which was coated with oleic acid.

[0102] Industrial applicability The method for preparing the mesh-like vertical graphene / carbon nanotube composite field emission cathode proposed in this invention has the following industrial application prospects: (1) Mature process and easy to scale up: Laser etching, plasma-enhanced chemical vapor deposition and chemical vapor deposition are all mature technologies in the semiconductor and vacuum coating fields. The equipment is highly versatile and can achieve grid-like mass production on large-area substrates to meet industrial needs.

[0103] (2) Excellent performance to meet high-end applications: The material of this invention has both a low turn-on electric field (<0.7 V / μm) and an ultra-high current density (>250 mA / cm). 2 It exhibits superior high-current stability (93% @ 60 min), far exceeding the performance of existing vertical graphene-based cold cathode materials. Specific applications include: Flat panel displays: As the electronic source for field emission displays, they enable high brightness, high resolution, and low power consumption.

[0104] X-ray source: Used for medical imaging and industrial non-destructive testing, providing a high-brightness, stable X-ray beam.

[0105] Microwave vacuum electronic devices, such as traveling wave tubes and klystrons, can be used as cold cathodes to replace traditional hot cathodes, enabling rapid startup and long lifespan.

[0106] Electron microscope: As a high-brightness, high-coherence electron emission source, it improves imaging resolution.

[0107] (3) Cost controllable: The nickel substrate used is inexpensive, the laser etching efficiency is high (seconds / square centimeter), the chemical vapor deposition process consumes little gas (several liters per hour), and the overall manufacturing cost is far lower than that of traditional Spindt cathodes (which require multiple complex processes such as photolithography, wet etching, and metal deposition).

[0108] (4) Strong customization capability: By adjusting the pattern of laser etching (number of pixels, scanning speed, pattern shape), the spatial distribution of the emitter can be flexibly controlled to meet the differentiated requirements of different application scenarios for emission current density and emission uniformity.

[0109] Therefore, this invention has clear industrial practical value and broad market prospects. The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a graphene / carbon nanotube composite material for a field emission cathode, characterized in that, Includes the following steps: (1) The nickel sheet is used as a substrate. It is polished to remove the surface oxide film and scratches. Then it is ultrasonically cleaned in acetone and alcohol respectively. Finally, it is dried with high-purity nitrogen. Then, the nickel sheet substrate is etched in a grid pattern by laser. The pattern shape of the nickel substrate is adjusted by controlling the number of pixels and the scanning speed of laser etching to obtain a grid-shaped nickel sheet substrate. (2) The mesh-like nickel sheet substrate obtained in step (1) is placed in a plasma-enhanced chemical vapor deposition chamber, heated in a reducing atmosphere, and carbon source gas is introduced to grow vertical graphene in situ on the surface of the mesh-like nickel sheet to obtain mesh-like vertical graphene. (3) Place the grid-like vertical graphene obtained in step (2) on the sample stage of the spin coater, and use spin coating to uniformly load the dispersion of oleic acid-coated iron oxide nanoparticles onto its surface, so that the dispersion can be fully spread and penetrate into the gaps and edge areas of the vertical graphene sheets; remove excess dispersion by high-speed rotation, control the catalyst loading and achieve uniform distribution of a single layer, heat and dry to remove solvent, and vacuum dry and heat after spin coating to remove the oleic acid ligands on the surface of the iron oxide nanoparticles, to obtain vertical graphene loaded with catalyst. (4) The vertical graphene loaded with catalyst obtained in step (3) is placed in a chemical vapor deposition furnace, and reducing gas and carbon source gas are introduced. By controlling the vapor growth temperature, time and carbon source gas, a field emission cathode material based on the in-situ growth of self-supporting carbon nanotube arrays of grid-like vertical graphene is finally obtained. The self-supporting carbon nanotubes have a length of 0.5-2 μm and an outer diameter of 10-50 nm. The spacing between adjacent carbon nanotubes in the array is 0.5-2 μm, forming a low-density, highly oriented array.

2. The preparation method according to claim 1, characterized in that, In step (1), the 0.5 mm thick nickel sheet is cut into 10×10 mm substrates and polished with 400 grit, 800 grit and 1200 grit sandpaper in sequence to remove the surface oxide film and scratches. Then, it is ultrasonically cleaned in acetone and alcohol for 15 minutes respectively, and repeated twice.

3. The preparation method according to claim 1, characterized in that, In step (1), the number of pixels etched by the laser is 50×50, 100×100, 150×150, 200×200, and the scanning speed is 50-800 mm / s.

4. The preparation method according to claim 1, characterized in that, In step (1), the pattern shape is a preset micron-level pattern, which can be a rectangular pattern, a rhombus pattern, a circular pattern, or a customized graphic.

5. The preparation method according to claim 1, characterized in that, In step (2), the growth conditions for the vertical graphene are: temperature 800-900℃, flow ratio of methane gas to hydrogen gas 1:(1-5), pressure 50-100 Torr, and time 0.5-2.0 h.

6. The preparation method according to claim 1, characterized in that, In step (3), the concentration of the iron oxide nanoparticle dispersion is 0.2-1.0 mg / mL, the solvent is n-hexane, and the spin coating process parameters are as follows: the first stage is a rotation speed of 300-800 rpm, preferably 500 rpm, for 5-15 s, so that the dispersion can be fully spread and penetrate into the gaps and edge areas of the vertical graphene sheets; the second stage is a rotation speed of 1000-4000 rpm, for 20-60 s, and the number of spin coatings is 1-5. Between each two spin coatings, the particles are heated and dried at 60-80℃ for 2-5 min to remove the solvent. After spin coating, the particles are vacuum dried and heated at 150-300℃ for 1-3 hours to remove the oleic acid ligands on the surface of the iron oxide nanoparticles, thus obtaining vertical graphene loaded with a catalyst.

7. The preparation method according to claim 1, characterized in that, In step (3), the nanocatalyst is a composite of one or more of iron oxide, cobalt oxide or nickel oxide, and its average particle size is 10-50 nm.

8. The preparation method according to claim 1, characterized in that, In step (4), a reducing gas and a carbon source gas are introduced at 700-800℃. The carbon source gas is methane, ethylene or acetylene, and the reducing gas is hydrogen. The flow ratio of the carbon source gas to the hydrogen is 1:(1-5). The growth temperature is 600-900℃ and the growth time is 0.5-2.0h.

9. A graphene / carbon nanotube composite material for field emission cathode prepared by the preparation method according to any one of claims 1-8.